2005
DOI: 10.1177/194589240501900508
|View full text |Cite
|
Sign up to set email alerts
|

Concordance of Middle Meatal Swab and Maxillary Sinus Aspirate in Acute and Chronic Sinusitis: A Meta-Analysis

Abstract: Endoscopic middle meatal cultures have a high concordance with MSAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 14 publications
3
35
0
1
Order By: Relevance
“…Th e bacteria species identifi ed in every microbiology study of chronic sinusitis are rarely associated with acute sinusitis or the acute exacerbation of chronic sinusitis, so the presence of bacteria on sinus mucosa should be interpreted as colonization rather than the infection [9]. Staphylococcus epidermidis is the bacteria that colonizes human body, including the oral cavity, so the majority of the authors of chronic sinusitis bacteriology studies assume this bacteria the contaminant and its presence in culture is usually discounted [10,11]. Comparing rates and species of bacteria found in chronic paranasal sinusitis with those found in normal maxillary sinuses, it is evident that there is no signifi cant diff erence between these two, suggesting that the same fl ora exists on the normal and chronically infl amed sinus mucosa [12].…”
Section: Discussionmentioning
confidence: 97%
“…Th e bacteria species identifi ed in every microbiology study of chronic sinusitis are rarely associated with acute sinusitis or the acute exacerbation of chronic sinusitis, so the presence of bacteria on sinus mucosa should be interpreted as colonization rather than the infection [9]. Staphylococcus epidermidis is the bacteria that colonizes human body, including the oral cavity, so the majority of the authors of chronic sinusitis bacteriology studies assume this bacteria the contaminant and its presence in culture is usually discounted [10,11]. Comparing rates and species of bacteria found in chronic paranasal sinusitis with those found in normal maxillary sinuses, it is evident that there is no signifi cant diff erence between these two, suggesting that the same fl ora exists on the normal and chronically infl amed sinus mucosa [12].…”
Section: Discussionmentioning
confidence: 97%
“…Finally, the microbes present in the middle meatus may not be entirely representative of the underlying sinuses. When compared to the “gold standard” of maxillary sinus puncture and aspirate, prior culture-based studies of middle meatus sampling in acute rhinosinusitis have demonstrated an accuracy in the 80-90% range [41-45], leading to the clinical practice recommendation for culture-directed antibiotics in the specialty care of CRS [46]. However, in the era of more sensitive culture-independent microbiologic techniques [5], and with the understanding that subtle alterations in the microenvironment may result in alterations in the local microbial communities, this acceptance must be critically re-examined.…”
Section: Discussionmentioning
confidence: 99%
“…Prior culture-based study has demonstrated that the middle meatus is about 80-90% representative of underlying sinuses in detection of colonizing bacteria [11-13]. Although not perfect, these results imply that microbial similarities exist between the middle meatus and underlying ethmoid and maxillary sinuses.…”
Section: Introductionmentioning
confidence: 93%